Self-Governance and Local Wisdom in Tourism Governance: Evidence from Samosir Regency - Agung Saputra; Siti Hajar; Sigit Hardiyanto; Noppawan Phuengpha (Journal Public Policy, 2026)
Efforts to improve tourism sustainability that integrates local cultural values, preserves the environment and empowers local communities. In the era of globalization, this approach is expected to prevent negative acculturation that can harm local identity. The purpose of this study is to explore and identify the principles of self-governance that can be implemented in tourism management in Samosir Regency, as well as to analyze its impact on local economic development. The method used in this study is a qualitative approach, in-depth interviews were conducted with FGDs with various stakeholders such as community leaders, tourism managers and local communities. The analysis was carried out using thematic analysis techniques to identify key issues and potentials. The results of the study indicate that the application of self-governance in tourism management can increase community participation in decision-making, strengthen local cultural identity, and increase economic benefits for local communities. In addition, this study found that local wisdom is a valuable asset that can be used as a foundation for sustainable tourism development. Therefore, cooperation between all stakeholders is needed to realize these goals.